THE EFFECT OF SENSORY STIMULI ON INCREASING CUSTOMER SATISFACTION AND CUSTOMER ADVOCACY BANKALTIMTARA USING THE Stimulus ORGANISM RESPONSE (SOR) MODEL - Dewi Nur Septyarini; Gusti Noorlitaria Achmad; Adjie Sofyan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Abstract: The purpose of this study is to prove that the Bankaltimtara website stimuli have an effect on the affective state of its customers, to prove that the Bankaltimtara's servicescape stimuli have an effect on the customer's affective state, to prove that the customer's affective state has an effect on increasing bankaltimtara's customer satisfaction. , to prove the affective state of customers mediating the influence of website stimuli on increasing customer satisfaction bankaltimtara, to prove the affective state of customers mediating the influence of website stimuli on increasing customer advocacy behavior bankaltimtara, to prove the affective state of customers mediating the effect of servicescape stimuli on increasing customer satisfaction bankaltimtara, to prove the situation customer affective mediates the effect of servicescape stimuli on increasing customer advocacy behavior ur bankaltimtara. This type of research uses survey research with a causative approach which aims to explain the causal relationship between two or more observed variables through hypothesis testing so that conclusions can be drawn. the population in this study were customers of conventional bankaltimtara savings. with Partial Least Square (PLS) program in data processing. the results of this study indicate that website stimuli have a positive and significant direct effect on the affective state of bankaltimtara customers, servicescape stimuli have a direct positive and significant effect on the affective state of bankaltimtara customers, affective state has a direct positive and significant effect on customer satisfaction bankaltimtara. Keywords: Effect Of Sensory Stimuli, Increasing Customer Satisfaction, Customer Advocacy, Stimulus Organism Response (SOR) Model, Bankaltimtara